Dining modes, satisfaction, and loyalty: evidence from Kuala Lumpur’s hybrid restaurants - Md Rus, Mohammad Hafizi; Abdul Latib, Nur Farrah Yasmin (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Hybrid dining models that integrate on-premise and off-premise services are increasingly shaping the restaurant industry in Kuala Lumpur. This study explores how on-premise attributes such as ambience, service quality, and menu variety, along with off-premise attributes including delivery speed, packaging quality, and order accuracy, influence customer satisfaction, and how satisfaction mediates their effects on customer loyalty. A cross-sectional survey was conducted with 384 customers who had recent hybrid dining experience, and data were analysed using Partial Least Squares Structural Equation Modeling (PLS- SEM). The results indicate that on-premise dining exerts a stronger positive influence on customer satisfaction compared to off-premise dining, and that satisfaction plays a central role in fostering loyalty by fully mediating the relationship between both dining modes and loyalty. These findings highlight the importance for restaurant operators to maintain high-quality in-store experiences while also optimising delivery operations to enhance customer retention. The study contributes to hospitality literature by integrating service quality and technology adoption perspectives into a unified hybrid dining framework, offering actionable strategies for customer loyalty in Malaysia’s evolving food service sector.